Estrutura populacional do Camarão Sete-Barbas Xiphopenaeus kroyeri (Heller, 1862), na Foz do Rio Itajaí-Açú, Itajaí, SC, Brasil - Branco,Joaquim Olinto (1999)
Xiphopenaeus kroyeri is the most exploited shrimp specie along Center-South coast of Santa Catarina State, Brazil, by artisanal fishery. In the period from March/1996 to February/1997, 3965 shrimps were collected (1843 males and 2122 females) sampled by over-trawl, with the depth oscillating between 5 and 15 meters. Xiphopenaeus kroyeri shows seasonal fluctuations in its abundance with higher rates in autumn. The population's average total-length varied between 7.5cm and 9.1cm, and the presence of juveniles was common along the year. The males and females get to the first gonadal maturation with 7.4 cm and 9.0 cm length, respectively; these lengths were reached within 6 and 8 months of age.